Pengembangan Modul Katekese Perkawinan Berbasis Keluarga Sebagai Fondasi Pendampingan Pasangan Muda Pasca-Pernikahan - Sember Sawo, Emilianus (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
This research aims to develop a family-based marriage catechesis module as a foundation for post-wedding accompaniment of young Catholic couples. Using a qualitative approach with document study, the research identifies five key gaps in Catholic couple accompaniment: discontinuity of pastoral care, non-transformative pedagogical approaches, minimal involvement of experienced families, lack of content contextualization, and weak communal support. In response, a module with spiral structure was developed for continuous accompaniment during the first four years of marriage, integrating theological-spiritual, relational-psychological, social-communal, and practical-contextual dimensions. This module operationalizes the concept of